Sapphire Blue - Gier, Kerstin; Bell, Anthea (Harrisonburg, Virginia Square Fish, 2013)
Sixteen-year-old Gwen, the newest and final member of the secret time-traveling Circle of Twelve, searches through history for the other time-travelers, aided by friend Lesley, James the ghost, Xemerius the gargoyle demon, and Gideon, the Diamond, whose fate seems bound with hers.
Keywords: Time travel -- Juvenile fiction; Families -- England; London; Juvenile fiction; Secret societies -- Juvenile fiction; London (England) -- Juvenile fiction; Great Britain -- History; Juvenile fiction; Fantasy fiction